Does inflammation predict successful pleurodesis? A post hoc analysis from the time 1 trial - Mercer, R; Macready, J; Jeffries, H; Speck, N; Kanellakis, N; Maskell, N; Pepperell, J; Saba, T; Ali, N; West, A; Miller, R; Asciak, R; et al. (BMJ Publishing Group, 2017)
Malignant pleural effusions are a common complication of advanced malignancy, have a poor prognosis and have a significant impact on quality of life. Treatment strategies include chest drain and pleurodesis, or insertion of an indwelling pleural catheter. Successful pleurodesis is thought to be due to the body’s inflammatory response resulting in pleural symphysis. This post hoc analysis of data from the TIME 1 was conducted to address assess whether there is a correlation between the pleurodesis and a systemic inflammatory response.